Real-Time Polymerase Chain Reaction: Applications in Diagnostic Microbiology - Kordo B. A. Saeed; Nusreen S. Ahmad (University Library System, University of Pittsburgh, 2013)
The polymerase chain reaction (PCR) has revolutionized the detection of DNA and RNA. Real-Time PCR (RT-PCR) is becoming the gold standard test for accurate, sensitive and fast diagnosis for a large range of infectious agents. Benefits of this procedure over conventional methods for measuring RNA include its sensitivity, high throughout and quantification. RT-PCR assays have advanced the diagnostic abilities of clinical laboratories particularly microbiology and infectious diseases. In this review we would like to briefly discuss RT-PCR in diagnostic microbiology laboratory, beginning with a general introduction to RT-PCR and its principles, setting up an RT PCR, including multiplex systems and the avoidance and remediation of contamination issues. A segment of the review would be devoted to the application of RT-PCR in clinical practice concentrating on its role in the diagnosis and treatment of infectious diseases.